2021
DOI: 10.3390/nu13114048
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Risk of Cystic Fibrosis-Related Diabetes: A Retrospective Single Center Cohort Study

Abstract: Objective: Cystic fibrosis-related diabetes (CFRD) affects up to half of the people with cystic fibrosis (CF) by adulthood. CFRD is primarily caused by pancreatic dysfunction that leads to insufficient insulin release and/or insulin resistance. Exocrine pancreatic insufficiency in people with CF is associated with fat-soluble vitamin malabsorption, including vitamins A, D, E, and K. This study examined the relationship between vitamin D status, assessed by serum 25-hydroxyvitamin D (25(OH)D), and the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…As such, the Cystic Fibrosis Foundation recommends annual measurement of serum 25(OH)D concentration [37, 38]. Vitamin D is associated with better skeletal health, lung function, and decreased risk of pulmonary exacerbations, cystic fibrosis-related diabetes, and infections [23, 37, 39, 40, 41]. Bolus vitamin D dosages are often required to increase serum 25(OH)D concentration in patients with CF, as patient adherence to other treatment options is lower [24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the Cystic Fibrosis Foundation recommends annual measurement of serum 25(OH)D concentration [37, 38]. Vitamin D is associated with better skeletal health, lung function, and decreased risk of pulmonary exacerbations, cystic fibrosis-related diabetes, and infections [23, 37, 39, 40, 41]. Bolus vitamin D dosages are often required to increase serum 25(OH)D concentration in patients with CF, as patient adherence to other treatment options is lower [24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate calcium absorption may be beneficial to decrease the risk of CFRD due to its ability to stimulate insulin release to the blood and its possible indirect effect on weight loss [1720]. Further, vitamin D 3 (cholecalciferol) supplementation has been associated with improved insulin secretion and decreased risk for CFRD [21, 22]. Hyperglycemia and insulin resistance can occur after illness, however, prior studies have not examined changes in glycemic control after treatment of a high-dose bolus of vitamin D 3 supplementation following an acute pulmonary exacerbation (APE).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate calcium absorption may be beneficial to decrease the risk of CFRD due to its ability to stimulate insulin release to the blood and its possible indirect effect on weight loss [24][25][26][27]. Further, in the context of CF, vitamin D 3 (cholecalciferol) supplementation has been associated with improved insulin secretion and decreased risk for CFRD [8,28]. In a systematic review of seven randomized control trials of children with obesity, four trials indicated that vitamin D supplementation had a positive impact on glycemic control as determined by insulin levels, insulin resistance, and fasting blood glucose [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other multiple organs, low levels of vitamin D3 are instead associated with increases in fibrosis in different pathologic conditions. 22 24 On the other hand, transforming growth factor β2 (TGF-β2) promotes the synthesis of COL1A1 in scleral fibroblasts. 25 Declines in TGF-β expression levels are likely associated with decreases in scleral collagen content during myopia development.…”
mentioning
confidence: 99%